Sex-Specific Differences of the Inflammatory State in Experimental Autoimmune Myocarditis - Barcena, Maria Luisa; Jeuthe, Sarah; Niehues, Maximilian H.; Pozdniakova, Sofya; Haritonow, Natalie; Kühl, Anja A.; Messroghli, Daniel R.; Regitz-Zagrosek, Vera (Frontiers in Immunology, 2021)
Increasing evidence suggests male sex as a potential risk factor for a higher incidence of cardiac fibrosis, stronger cardiac inflammation, and dilated cardiomyopathy (DCM) in human myocarditis. Chronic activation of the immune response in myocarditis may trigger autoimmunity. The experimental autoimmune myocarditis (EAM) model has been well established for the study of autoimmune myocarditis, however the role of sex in this pathology has not been fully explored. In this study, we investigated sex differences in the inflammatory response in the EAM model. We analyzed the cardiac function of, as well as the inflammatory stage and fibrosis formation in the heart of EAM male and female rats. 21 days after induction of EAM, male EAM rats showed a decreased ejection fraction, stroke volume and cardiac output, while females did not. A significantly elevated number of infiltrates was detected in myocardium in both sexes, indicating the activation of macrophages following EAM induction. The level of anti-inflammatory macrophages (CD68+ ArgI+) was only significantly increased in female hearts. The expression of Col3A1 and fibrosis formation were more prominent in males. Furthermore, prominent pro-inflammatory factors were increased only in male rats. These findings indicate sex-specific alterations in the inflammatory stage of EAM, with a pro-inflammatory phenotype appearing in males and an anti-inflammatory phenotype in females, which both significantly affect cardiac function in autoimmune myocarditis.